PENGARUH METODE PROJECT BASED LEARNING TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 1 PENANGGALAN KOTA SUBULUSSALAM - Nurdiana; Telaumbanua, Sadieli; Sari, Sartika (Universitas Hamzanwadi, 2024)
This study aims to compare the writing abilities of students in writing Explanatory Texts using the lecture method and the project-based learning method among eighth-grade students at SMP Negeri 1 Penaggalan for the 2023-2024 academic year. This research employs a Quasi-Experimental method involving two groups, namely the experimental class and the control class. Data analysis revealed that the post-test scores of students in the experimental class had an average score of 80.71, with the highest score being 95 and the lowest score being 65. Data showed that 29 students scored above the minimum competency criteria (KKM), while 7 students did not meet the KKM. An inferential test and hypothesis test were conducted to determine the differences in students' abilities to write Explanatory Texts using the project-based learning method and the lecture method. Inferential tests indicated that both classes were normally distributed and homogeneous. The hypothesis test using an independent sample test revealed two key findings: the Sig. (2-tailed) value was 0.00 < 0.05. Additionally, based on the t-test assumption, the calculated t-value was greater than the t-table value with α = 0.05 degrees of freedom (df = 69), yielding t calculated > t table at 5.819 > 1.667. The hypothesis test results indicated that Ha was accepted. From these results, the hypothesis or research conclusion states,